Psychiatrists and GPs: diagnostic decision making, personality profiles and attitudes toward depression and anxiety. (June 2013) - Lampe, Lisa; Fritz, Kristina; Boyce, Philip; Starcevic, Vladan; Brakoulias, Vlasios; Walter, Garry; Shadbolt, Narelle; Harris, Anthony; Malhi, Gin
Objectives: The objective of this article is to explore diagnostic decision making around psychological symptoms presenting to general practitioners (GPs) and psychiatrists, identify attitudinal and personality factors of possible relevance in these decisions, and compare GPs and psychiatrists to help identify potential educational targets. Methods: GPs and psychiatrists attended separate peer-facilitated workshops in which two case presentations were discussed. Decision making was explored by structured questions embedded in the workshop, with responses recorded by electronic keypad technology. Participants completed demographic questionnaires and measures of personality and attitudes to depression. Results: GPs and psychiatrists accorded emphasis to different elements of the history, and assigned different diagnoses based on the same set of symptoms. Both groups relied on non-pharmacological management for milder psychological symptoms; GPs were less likely to make a diagnosis of bipolar disorder. Traits of Extraversion and Agreeableness were associated with greater ease in treating depression. Conclusions: Differences in diagnostic decision making likely reflect the different contexts of specialist and generalist practice. Educational targets may include information about key symptoms to assist in diagnostic precision, but further information is needed to determine the best match between diagnostic processes, context and outcome. An awareness of the role of personality factors may help when designing education and support programs.